Functionally Convergent B Cell Receptor Sequences in Transgenic Rats Expressing a Human B Cell Repertoire in Response to Tetanus Toxoid and Measles Antigens - Bürckert, Jean-Philippe; Dubois, Axel R. S. X.; Faison, William J.; Farinelle, Sophie; Charpentier, Emilie; Sinner, Regina; Wienecke-Baldacchino, Anke; Muller, Claude P. (Frontiers in Immunology, 2017)
The identification and tracking of antigen-specific immunoglobulin (Ig) sequences within total Ig repertoires is central to high-throughput sequencing (HTS) studies of infections or vaccinations. In this context, public Ig sequences shared by different individuals exposed to the same antigen could be valuable markers for tracing back infections, measuring vaccine immunogenicity, and perhaps ultimately allow the reconstruction of the immunological history of an individual. Here, we immunized groups of transgenic rats expressing human Ig against tetanus toxoid (TT), Modified Vaccinia virus Ankara (MVA), measles virus hemagglutinin and fusion proteins expressed on MVA and the environmental carcinogen Benzo[a]Pyrene, coupled to TT. We showed that these antigens impose a selective pressure causing the Ig Heavy chain (IgH) repertoires of the rats to converge towards the expression of antibodies with highly similar IgH CDR3 amino acid sequences. We present a computational approach, similar to differential gene expression analysis, that selects for clusters of CDR3s with 80% similarity, significantly overrepresented within the different groups of immunized rats. These IgH clusters represent antigen-induced IgH signatures exhibiting stereotypic amino acid patterns including previously described TT and measles specific IgH sequences. Our data suggest, that with the presented methodology, transgenic Ig rats can be utilized as a model to identify antigen-induced, human IgH signatures to a variety of different antigens.